2006
DOI: 10.1074/jbc.m600440200
|View full text |Cite
|
Sign up to set email alerts
|

Low Affinity Analogs of Thyrotropin-releasing Hormone Are Super-agonists

Abstract: We show that several analogs of thyrotropin-releasing hormone (TRH) are more efficacious agonists at TRH receptors R1 and R2 than TRH itself. The apparent efficacies of the analogs were inversely related to their potencies and were independent of the nature of the modifications in TRH structure. In studies in intact cells, we showed that the differences in apparent efficacies were not due to differences in G-protein coupling, receptor desensitization, or recycling. Moreover, the differences in efficacies persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…The generation of a HEK-EM293 cell lines stably expressing human TSHR (HEK-TSHR cells) or human TRH receptor were described previously (Engel et al, 2006;Neumann et al, 2009). Cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, 100 U/ml penicillin, and 10 g/ml streptomycin and 250 g/ml hygromycin B (both from Invitrogen, Carlsbad, CA) at 37°C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of a HEK-EM293 cell lines stably expressing human TSHR (HEK-TSHR cells) or human TRH receptor were described previously (Engel et al, 2006;Neumann et al, 2009). Cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, 100 U/ml penicillin, and 10 g/ml streptomycin and 250 g/ml hygromycin B (both from Invitrogen, Carlsbad, CA) at 37°C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…shares properties with other synthetic ligands that have been shown to have higher intrinsic activity than their respective endogenous ligands, such as the non-peptide growth hormone secretagogue MK-677 (Bennett et al, 2009;Holst et al, 2005) and the thyrotropin-releasing hormone analogue R-Des-TRH (Engel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…If such a case were true, the maximal asymptote of the concentration-response curves of endogenous agonists, fitted to experimental data (Strange, 2008) (intrinsic activity, E max ), would always be equal to the system maximum. However, there are a class of synthetic ligands such as MK-677 at the GNRH receptor or R-Des-TRH at the TRH receptor (Bennett et al, 2009;Engel et al, 2006) that have been demonstrated to produce higher maximal responses than their respective endogenous ligands, leading to the term super agonist being coined. Such terminology has been met with mixed views in the pharmacology community, and the unique pharmacology of super agonists is now the subject of increasing interest and debate.…”
Section: Introductionmentioning
confidence: 99%
“…12,24 Jain et al have reported the synthesis of TRH analogs in which both pGlu and central histidine residue was simultaneously modified. 25,26 Gershengorn and Jain et al 27,28 have showed for the first time that certain TRH analogs were more efficacious agonists at TRH-R1 and TRH-R2 than TRH itself. They found that decrease in the affinities caused by TRH analogs correlate inversely with the analog ability to activate TRH-Rs.…”
Section: Introductionmentioning
confidence: 97%